Psychological method and the historical Jesus: The contribution of psychobiography - Os, Bas van (HTS teologiese studies, 2007)
This article reviews a number of psychologically informed studies of Jesus in view of the criteria pertaining to psychobiography. It argues that the studies have produced divergent interpretations of Jesus because of a lack of data and the nature of the sources. This is especially true of these studies as they used psychological approaches based on childhood experiences. The framework for psychobiography also allows for the use of other methods that are more concerned with religious adults in coping situations. These may be applied to explore theories about the psychological development of the adult Jesus. The article shows also that the use of the New Testament sources also implies assumptions with regard to the nature of these sources and the people who had produced those sources.